2021
DOI: 10.3390/ijerph18105288
|View full text |Cite
|
Sign up to set email alerts
|

Updating Standards of Facial Growth in Romanian Children and Adolescents Using the Anthropometric Method—A Pilot Study

Abstract: The anthropometric method is an important tri-dimensional and non-invasive assessment instrument for accurate diagnosis in paedodontics, orthodontics, and other medical fields. Our aim was to propose a technique that is accessible for clinicians and to determine the reference values for Romanian children and adolescents for the facial parameters selected. We proposed three basic instruments: a plastic compass, a ruler, and a digital caliper. Eighty-five children and adolescents (62% girls and 38% boys), aged b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
2
2
Order By: Relevance
“…The mean facial depth was found to be 89mm, equivalent to that given by Sforza 8 in children with deciduous dentition. But an anthropometrical analysis in children 17 and a photogrammetry study among adults showed much higher values to that of what we obtained. Facial parameters like anterior upper facial height, upper facial width, mouth width, nasal depth and facial depth did not contribute much to attractiveness in healthy children.…”
Section: Facial Depthcontrasting
confidence: 88%
See 1 more Smart Citation
“…The mean facial depth was found to be 89mm, equivalent to that given by Sforza 8 in children with deciduous dentition. But an anthropometrical analysis in children 17 and a photogrammetry study among adults showed much higher values to that of what we obtained. Facial parameters like anterior upper facial height, upper facial width, mouth width, nasal depth and facial depth did not contribute much to attractiveness in healthy children.…”
Section: Facial Depthcontrasting
confidence: 88%
“…It signifies nasal length and Indian nose should be considered as a different entity in comparison to those of Caucasian, Oriental, and African populations. 16 The average value was found to be approximately 49mm in the present study whereas in a 3D facial morphometric study, it ranged between 36.7-40.4mm8 and an anthropometric study 17 on Romanian children showed values ranging from 31-43 mm. Thus, the variation in the average values can be attributed to difference in the ethnicity, as an average Indian exhibits increased nasal length.…”
Section: Anterior Upper Facial Heightcontrasting
confidence: 58%
“…17 Ogodescu E et al reported mouth width as 35.93 ± 3.43mm in 3.5-5years old children and 44.14 ± 3.93mm in 11.5-13 years old normal Romanian children. 26 Esmaeilzadeh Mahdi found 35.1±2.5 mm. to 44.1 ± 3,5 mm mouth width in children aged from 4-11 years old.…”
Section: Discussionmentioning
confidence: 94%
“…16 Jahanbin A et al found alar width from 24.33 ±2.60mm in children less than one year to 32.90 ±2.15mm in 11years old children with a difference of 2.0 to 4.0mm while compared to current study 26.07±3.81 and 36.4±1.4mm respectively. 17 22,26 Mouth Width: Zreaqat M et al reported 48.9 ±3.69mm mouth width in children having orofacial clefts while in children with normal morphology it was found as 50.3±5.72mm with no statistical significance. 16 The current study reported 28.35 ±1.82mm to 39.27±1.42mm mouth width in children with orofacial clefts from three months to 13years.…”
Section: Discussionmentioning
confidence: 99%
“…Stunting is a condition that indicates a lack of intake and a long incidence of infectious diseases [3]. Stunting is assessed with a z-score of Height for Age (TB/U) showing <-2 standard deviation (SD) [4]. At the age of 24-59 months, the physical manifestations of stunting will be more visible [5].…”
Section: Introductionmentioning
confidence: 99%